Genocide and resistance Nr. 26(2) - Rukšėnas, Alfredas; Buchaveckas, Stanislovas; Pušinskytė, Lijana; Streikus, Arūnas; Banionis, Juozas; Juodis, Darius; Okuličiūtė, Lina; Tamošaitis, Mindaugas (Genocidas ir rezistencija, 2009)
Full Issue